High Order Gene-Gene Interactions in Eight Single Nucleotide Polymorphisms of Renin-Angiotensin System Genes for Hypertension Association Study. (19th April 2015) - Yang, Cheng-Hong; Lin, Yu-Da; Wu, Shyh-Jong; Chuang, Li-Yeh; Chang, Hsueh-Wei
Abstract : Several single nucleotide polymorphisms (SNPs) of renin-angiotensin system (RAS) genes are associated with hypertension (HT) but most of them are focusing on single locus effects. Here, we introduce an unbalanced function based on multifactor dimensionality reduction (MDR) for multiloci genotypes to detect high order gene-gene (SNP-SNP) interaction in unbalanced cases and controls of HT data. Eight SNPs of three RAS genes (angiotensinogen, AGT ; angiotensin-converting enzyme, ACE ; angiotensin II type 1 receptor, AT 1 R ) in HT and non-HT subjects were included that showed no significant genotype differences. In 2- to 6-locus models of the SNP-SNP interaction, the SNPs of AGT and ACE genes were associated with hypertension (bootstrapping odds ratio [Boot-OR] = 1.972~3.785; 95%, confidence interval (CI) 1.26~6.21; P < 0.005 ). In 7- and 8-locus model, SNP A1166C of AT 1 R gene is joined to improve the maximum Boot-OR values of 4.050 to 4.483; CI = 2.49 to 7.29; P < 1.63 E − 08 . In conclusion, the epistasis networks are identified by eight SNP-SNP interaction models. AGT, ACE, and AT 1 R genes have overall effects with susceptibility to hypertension, where the SNPs of ACE have a mainly hypertension-associated effect and show an interacting effect to SNPs of AGT and AT 1 R genes.